Coin images and public life in Republican Rome - Barbosa, Gisele Oliveira Ayres (Romanitas - Revista de Estudos Grecolatinos, 2019)
This paper deals with the relation between public life and coin images based on two Republican denarii. These pieces were issued by Caius and Tiberius Minucius Augurinus in 135 and 134 BCE, respectively. It adopts the perspective of a dynamic second century in a Roman Republic in ongoing internal transformation, as proposed by H. Flower (2010). It is within the assumption that, in the numismatic iconography of the period, what we call “religion” and what we call “politics” staged together a common discourse that, in different ways, tell us about the city of Rome and its citizens.